Florid cemento osseous dysplasia and dentygerous cyst in a patient with apert syndrome: A case report - Nazlıcan Paslı; Fatma Nihan Aksakallı; Ender İdman; M. Oğuz Borahan; Emrah Canbazoğlu; Hasan Garip; Şebnem Erçalık Yalçınkaya (Selcuk Dental Journal)
Apert syndrome is a rare congenital malformation characterized by craniocinocytosis, craniofacial anomalies and symmetric syndactyly of the feet and hands. Oral manifestations of Apert syndrome usually represents bifid uvula, malposition of the teeth, severe open bite, tooth decay and periodontal diseases. Fluorid cemento-osseous dysplasia is usually asymptomatic slow-growing non-neoplastic fibro-osseous lesions. Lesions are detected by routine radiographic examination. The aim of this case report is to present dentigerous cyst and florid cemento-osseous displasia in a patient with Apert syndrome. A 38-year-old female patient with a history of Apert syndrome referred to Marmara University, Faculty of Dentistry, Clinic of Oral and Dentomaxillofacial Radiology due to pain and swelling. On panoramic radiography, unilocular, hyperdense lesion with regular borders was observed in the anterior region of the mandible. Cone-beam computed tomography (CBCT) was performed for further examination of the lesion and perforation of buccal bone cortex was seen. Additionally, a regular monolocular hypodense lesion was observed in the anterior region of maxilla. A biopsy was performed to examine the lesion histopathologically. Histopathologic examination was performed to evaluate the lesions and the lesion in the mandible was diagnosed as cemento-osseous dysplasia. Because the lesion was multifocal, it was considered and compatible with fluoride cemento-osseous dysplasia. The lesion in the maxilla was diagnosed as dentigerous cyst on histopathologic examination. The diagnosis of fluoride cemento-osseous dysplasia is established by definite radiological and histopathological evaluation. In asymptomatic cases of fluorid cemento-osseous dysplasia, treatment is not required but patients should be followed up regularly. Practitioners should take into consideration the oral and dental findings in patients with Apert syndrome which rarely appear.KEYWORDS